AB0623 Assessment of bone mineral density and fracture risk in patients awaiting liver transplantation. (23rd January 2014) - Heredia, S.; Nolla, J. M.; Baliellas, C.; Llado, L.; Gómez-Vaquero, C.
Abstract : Background: The patients who have undergone a liver transplantation (LT) have a high prevalence of osteoporosis (30%) and fragility fractures (7-35%), mainly during the first year after LT. Currently, it is recommended to perform a bone densitometry (BD), an analytical study including parameters of bone metabolism and a lateral X-ray of thoracolumbar spine in patients awaiting LT. Antiresorptive or bone forming drugs are usually indicated in case of fragility fracture or T-score ≤ -1.5 SD in lumbar spineor proximal femur. Objectives: To define the clinical and densitometric characteristics of patients awaiting LT. To assess who of them meet the criteria for referral to a specialized unit in bone metabolism or the treatment indications to prevent fragility fractures. Methods: SinceJuly 2010, in patients awaiting LT, we perform systematically a lumbar spine and proximal femur DXA scanning and we record their fracture risk factors. Since June 2012, patients with T-score ≤ -1.5 SD at the lumbar spine or proximal femur or history of fragility fracture are cited in a specialized outpatient clinic in bone metabolism. Patients are well characterized regarding their liver disease and ongoing hepatic function. The study protocol included the determination of general and liver laboratory parameters and the assessment of the hepatic functionalism evaluated by the Child-Pugh scale and the Model for End-Stage Liver Disease (MELD) score [values ranging from 6 to40 (the lower score, the better prognosis and the lower priority in the awaiting list)]. We have calculated the absolute risk of having a major or hip fracture (MRF/HRF) in the following 10 years with the Spanish version of the FRAX tool, both including and not bone mineral density (BMD) in the algorithm. Results: We identified157 patients (80% male) with a mean age of 55 ± 8 years and a body mass index (BMI) of 26.6 ± 4.2 kg/m2. The main underlying diseases that led to get on the awaiting list were alcoholic liver disease (58%) and hepatitis C virus chronic hepatitis (48%). Patients were classified according to theChild Pugh scale: 32% class A, 35% class B and 33% class C. The mean MELD score was 16.26 ± 6.29. Thirty-seven percent had a normal BMD, 44% had osteopenia and 19% osteoporosis. Twenty percent had experienced a fragility fracture. The MRF was 2.9 ± 1.8% and the HRF, 0.7 ± 1.3%; without including BMD in the FRAX algorithm, 2.8 ± 1.5% and 0.6 ± 0.7%, respectively. Eighty (51%) patients had at least one of the criteria for referral to a specialized outpatient clinic in bone metabolism. Finally, we began supplements ofcalcium and vitamin D in 56 patients and treatment with bisphosphonates in 31. The FRAX tool was not useful for determining which patients should be scanned by DXA. Patients who received treatment to prevent a osteoporotic fracture had a T-score below -1.5 SD and a lower BMD than the others; they were not different with respect to age, BMI, WHO classification, Child-Pugh scale or MELD score. Conclusions: The prevalenceof osteoporosis and fragility fracture in patients awaiting LT is high. Half of the patients have at least one of the criteria for referral to a specialized outpatient clinic in bone metabolism. None of the liver function tests or FRAX tool help to predict which patients will be candidates for a diagnostic or therapeutic intervention. Disclosure of Interest: None Declared